Need Analysis of Gamification-Based E-Learning Development with ADDIE Method for Student Learning Using Moodle Platform - Priadi, Yohanes; Yosua Arda Kurnia; Benedictus Pascal Sanjaya (Politeknik Piksi Ganesha Indonesia, 2024)
A major challenge in e-learning is maintaining student motivation and engagement in the learning process. Gamification has been proven to be an effective approach in increasing student motivation by adding game elements into the learning experience. This research aims to analyze the needs of gamification-based e-learning development for student learning using ADDIE (Analysis, Design, Development, Implementation and Evaluation) method on Moodle platform. Moodle was chosen because it supports various gamification plugins, such as Level Up XP, Block Game, Ludic, Quizventure, Game and Badge Ladder. Through a comprehensive needs analysis, this research produces an appropriate design to improve learning engagement and effectiveness. The results of this research are expected to provide guidance for the development of gamification-based e-learning that is optimal for student learning.